EDICOLEGAL STUDY ON THE VERIFICATION OF THE SUBCUTANEOUS HEMORRHAGE BY THE AMOUNT OF IRON IN A DECAYED DEAD BODY - Taek, M D O In; Chol, Pak Hun (Journal of Forensic Medicine and Toxicology, 2024)
This is a perspective study of 70 cadavers to identity hemorrhages by shaming iron an uncial. The amount of them normal tissue is 20 μg/g in skin and 40 μg in muscle. In bleeding carry it is 35 μg/g in skin and 53 gm/g in muscle the amount of iron in the injured pant in 3.5 times hyaline than in normal tissue.
Keywords: Detection & hemorrhage in dead; iron concencentrain in injuries